Lucius phenomenon: the importance of a primary dermatological care - Juliana Viana Pinheiro; Maria Araci de Andrade Pontes; José Urbano de Medeiros Neto; Heitor de Sá Gonçalves (Sociedade Brasileira de Dermatologia, 2022)
Abstract Leprosy presents a varied clinical spectrum. Lucius phenomenon is a rare leprosy reaction characterized by erythematous, painful, slightly infiltrated macules and hemorrhagic bullae that progress to ulceration. This case report describes a patient whose diagnosis of leprosy occurred in the presence of Lucius phenomenon. Late diagnosis and delay in the implementation of specific therapy contributed to an unfavorable outcome, highlighting the importance of early identification and treatment of this disease, as well as its complications.